Ketepatan waktu pembayaran simpan pinjam guna meningkatkan pengembangan koperasi unit desa - Prastika Nurlitaputri; Isharijadi Isharijadi; Elana Era Yusdita (Journal of Business & Banking, 2020)
This study aims to analyze (1) the causes of inaccurate loan payments (2) the handling of inaccurate savings and loan payments (3) solutions for the development of the SMW Village Unit Cooperative. The data were collected by means of observations, interviews, and documentation. Then, they were analysed using descriptive analysis with a qualitative approach. The informants of this study were the cooperative employees in relation whith the cooperative savings and loan process. The results showed that the inaccurate loan repayments were due to economic factors (illness, celebration, disaster experienced by members, other unexpected needs) and delayed harvest periods (crop failure). The handling of inaccurate savings and loan payments done by the KUD SMW were taken by conducting field surveys, giving warnings, and taking personal approaches. Next is that the solution to developing the KUD SMW is carried out by means of business expansion and business intensification. The SMW KUD should do a more maximal analysis of the 5C principle so that they can clearly identify the borrower's ability to pay their future obligations, and it is better to strengthen the development of business intensification prior to business extentification so that bad credit does not burden new business units.